ANALISIS PEMANFAATAN LIMBAH TERNAK UNTUK BIOGAS DALAM UPAYA MENGURANGI PENGELUARAN RUMAH TANGGA MASYARAKAT DESA GIRI MULYO KECAMATAN KAYU ARO BARAT - Zasriati, Masrida (EDUTECH CONSULTANT, 2018)
The purpose of this study refers to: (1) determine the amount of household expenditures to fuel the kitchen before the uses of biogas, (2) the expenditures of households to fuel the kitchen after the uses of biogas, and (3) determine the amount of the reduction of kitchens household expenditure using biogas fuel. The results showed: (1) the amount of fuel expenditures household kitchen's before using biogas average of Rp. 269 ​​516 per month. (2) the amount of fuel expenditures household kitchen's after using biogas average of Rp. 92 581 per month, (3) a reduction in fuel expenditure household in the village of Giri Mulyo after using biogas amounted to Rp. 5.485 million or an average of Rp. 176 935 per month / families or assuming a reduction in fixed expenditure then the average of Rp 176,935 x 12 equals 2,123,225 per year / families.